Implementation of 360° Virtual Reality using Sky View as Information Media for Infrastructure Infrastructure in Education Sector - Latifah, Ayu; Rizal Nurul Hadi, Muhamad (APIC, 2025)
The rapid advancement of information technology has had a significant impact on various sectors, including education. One educational institution in Garut, Yayasan Al Musaddadiyah, faces challenges in effectively conveying information to prospective students. Traditional media such as brochures and pamphlets often fail to provide a comprehensive depiction and better visualization of the facilities and educational environment at the institution. As a solution, this research developed a Virtual Reality (VR) 360° media with a Sky View perspective to visualize the existing facilities and infrastructure at Yayasan Al Musaddadiyah. The study utilized the Multimedia Development Life Cycle (MDLC) method in the VR application development process. MDLC was chosen because it provides a systematic approach at each development stage, from concept to implementation and evaluation. In this research, various multimedia elements such as images, videos, and audio were integrated into the VR application to create an immersive and interactive experience for users. By leveraging VR 360° Sky View technology, prospective students and parents can directly view the educational environment and available facilities at the institution without physically visiting the location. Evaluation results showed that the use of VR-based information media successfully increased the interest and understanding of prospective students towards Yayasan Al Musaddadiyah. Additionally, this application proved effective in expanding the reach of information about the institution, particularly in the increasingly connected digital era. Thus, the development of VR-based information media not only provides a practical solution to the institution’s communication challenges but also opens up new opportunities as a promotional or marketing strategy for educational institutions in the future.